2020
DOI: 10.1007/s11270-020-04721-9
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate and Monodentate Binding of Chromium (VI) on the Acid Scavenger Exchange Resin, MP-Carbonate, as a Function of pH

Abstract: Hexavalent chromium or Cr (VI) is a serious health risk that has been identified in drinking water and generally originates as industrial by-products and hazardous waste sites, although natural sources have been reported. Common methods to remove Cr (VI) employ adsorption, filtration, ion exchange technologies, and redox reactions. We report on a macro porous polystyrene anion exchange resin, a solid-supported equivalent of tetra-alkyl ammonium carbonate (Biotage® MP-Carbonate), to effectively remove Cr (VI) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated the potential of zero-valent iron [10], iron oxide [11], and magnetitebased sorbents [12] for the removal of chromate anions. Synthetic resins (chelating [13] or ion-exchange [14,15] have been frequently used for the recovery of chromate anions. Composite beads prepared by the interactions of alginate with polyethyleneimine have also been recently designed as beads for the effective recovery of Cr(VI) [16].…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…Many studies have demonstrated the potential of zero-valent iron [10], iron oxide [11], and magnetitebased sorbents [12] for the removal of chromate anions. Synthetic resins (chelating [13] or ion-exchange [14,15] have been frequently used for the recovery of chromate anions. Composite beads prepared by the interactions of alginate with polyethyleneimine have also been recently designed as beads for the effective recovery of Cr(VI) [16].…”
Section: Characterization Of Materialsmentioning
confidence: 99%